2008
DOI: 10.1097/mat.0b013e31815b2d1e
|View full text |Cite
|
Sign up to set email alerts
|

Acute In Vivo Evaluation of an Implantable Continuous Flow Biventricular Assist System

Abstract: An implantable biventricular assist device offers a considerable opportunity to save the lives of patients with combined irreversible right and left ventricular failure. The purpose of this study was to evaluate the hemodynamic and physiologic performance of the combined implantation of the CorAide left ventricular assist device (LVAD) and the DexAide right ventricular assist device (RVAD). Acute hemodynamic responses were evaluated after simulating seven different physiological conditions in two calves. Evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Based on our previous animal nonpulsatile perfusion studies using continuous-flow BVAD support of a fibrillated heart, it was shown that pulmonary circulation was maintained at 2 to 3 L/min with the RVAD pump off and the heart fibrillated 15. This residual flow may be explained by the presence of the so called “atrial kick”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous animal nonpulsatile perfusion studies using continuous-flow BVAD support of a fibrillated heart, it was shown that pulmonary circulation was maintained at 2 to 3 L/min with the RVAD pump off and the heart fibrillated 15. This residual flow may be explained by the presence of the so called “atrial kick”.…”
Section: Discussionmentioning
confidence: 99%
“…This BVAD control mode is particularly challenging as one must maintain proper right-left flow and atrial pressure balance. We have previously shown, in acute bovine BVAD experiments looking at the effects of varying levels of left and right ventricular support, the importance of adjusting the left pump speed and flow to be higher than that of the right pump and limiting the RVAD maximum operating speed to 2,400 rpm to avoid possible imbalance between right and left circulation 15. In our DexAide/CorAide BVAD control scheme, the CorAide pump is set to automatic mode, in which the pump speed is adjusted to obtain a target flow, while using the flow pulsatility to avoid possible left ventricular suction.…”
Section: Discussionmentioning
confidence: 99%
“…68 However, the few documented clinical studies of rotary biventricular support warn of hemodynamic instability. 13,47,48,58,77 All report the importance of continued controller development to prevent pulmonary edema and incidence of suction events in the cannulated heart chamber. Clearly then, balancing of circuit volumes is crucial for any rotary support device, especially rotary BiVADs.…”
Section: Requirement For Biventricular Supportmentioning
confidence: 98%
“…The CoreAide has a displacement volume of 84 mL, pump weight of 293 g, a portable power supply (6 h battery life), and controller weight of 1350 g. 58 It can achieve flow rates from 2 to 8 L min 21 and has an operational pump speed range of 2000-3000 RPM. Pumping 5 L min 21 against 100 mmHg, the CorAide LVAD uses less than 6 W of power at 2850 RPM.…”
Section: Coraide/dexaidementioning
confidence: 99%
“…CFBVAD support was investigated in our acute hemodynamic animal testing (CorAide CFLVAD and DexAide CFRVAD), in which we evaluated calf hemodynamics and physiologic response at baseline and for six different hemodynamic conditions of vasoconstriction, vasodilation, low circulating blood volume, and varying degrees of heart failure (35). The predominant pathophysiologic effect of independently varying DexAide and CorAide pump speeds was the marked sensitivity of left atrial pressure to increasing CFRVAD speed above 2,400 rpm.…”
Section: Lesson Learned In Design and Animal Testing Of A Permanent Imentioning
confidence: 99%